Why Later Wittgenstein was not a therapist - Loughlin, Victor (Aufklärung: journal of philosophy, 2021)
Wittgenstein famously regarded philosophy as an activity and not as a body of doctrine. And yet within the secondary literature there is little agreement as to what Wittgenstein took the purpose of that activity to be. In this paper, I claim that the purpose of philosophical activity, at least according to the Later Wittgenstein, was to solve philosophical problems. As support for this claim, I argue that our everyday talk about the mind presents us with a philosophical problem about the mind. Focusing then on what Wittgenstein says about understanding and using his distinction between internal and external relations, I show how we can solve this problem. If my reading is accepted, then the purpose of philosophical activity, according to the later Wittgenstein, was not therapy. As such, later Wittgenstein should not be read as a therapist.